Tissue-specific and transcription-dependent mechanisms regulate primary microRNA processing efficiency of the human chromosome 19 MicroRNA cluster - Fóthi, Ábel (RNA Biol, 2020)
One of the longest human microRNA (miRNA) clusters is located on chromosome 19 (C19MC), containing 46 miRNA genes, which were considered to be expressed simultaneously and at similar levels from a common long noncoding transcript. Investigating the two tissue types where C19MC is exclusively expressed, we could show that there is a tissue-specific and chromosomal position-dependent decrease in mature miRNA levels towards the 3ʹ end of the cluster in embryonic stem cells but not in placenta. Although C19MC transcription level is significantly lower in stem cells, this gradual decrease is not present at the primary miRNA levels, indicating that a difference in posttranscriptional processing could explain this observation. By depleting Drosha, the nuclease component of the Microprocessor complex, we could further enhance the positional decrease in stem cells, demonstrating that a tissue-specific, local availability of the Microprocessor complex could lie behind the phenomenon. Moreover, we could describe a tissue-specific promoter being exclusively active in placenta, and the epigenetic mark analysis suggested the presence of several putative enhancer sequences in this region. Performing specific chromatin immunoprecipitation followed by quantitative real-time PCR experiments we could show a strong association of Drosha with selected enhancer regions in placenta, but not in embryonic stem cells. These enhancers could provide explanation for a more efficient co-transcriptional recruitment of the Microprocessor, and therefore a more efficient processing of pri-miRNAs throughout the cluster in placenta. Our results point towards a new model where tissue-specific, posttranscriptional ‘fine-tuning’ can differentiate among miRNAs that are expressed simultaneously from a common precursor.